2019
DOI: 10.1002/jaba.631
|View full text |Cite
|
Sign up to set email alerts
|

Differential reinforcement‐of‐low‐rate procedures: A systematic replication with students with autism spectrum disorder

Abstract: and Castillo (2018) studied the effects of two different types of DRL schedules (full session and spaced responding) under 2 sets of stimulus conditions (with and without signals). Reduced rates of responding maintained under both types of DRL schedules, when signals were included. The present study represents a replication of procedures by Becraft et al. involving learners with autism spectrum disorder (ASD). The results replicated those of Becraft et al. in that responding in both full-session and spaced-res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Piper et al [ 33 ] replicated procedures involving learners with ASD in that responding in both full-session and spaced-responding differential reinforcement of low rates of behavior (DRL) schedules were low but not eliminated. Their results provided preliminary evidence to suggest that children with ASD are responsive to signals in DRL arrangements, which may set the stage for evaluating signaled DRL arrangements for socially significant response forms.…”
Section: Discussionmentioning
confidence: 99%
“…Piper et al [ 33 ] replicated procedures involving learners with ASD in that responding in both full-session and spaced-responding differential reinforcement of low rates of behavior (DRL) schedules were low but not eliminated. Their results provided preliminary evidence to suggest that children with ASD are responsive to signals in DRL arrangements, which may set the stage for evaluating signaled DRL arrangements for socially significant response forms.…”
Section: Discussionmentioning
confidence: 99%
“…Full-session DRL is defined as reinforcement contingent on the targeted behavior occurring less often than a specified frequency throughout an entire measurement period, or session (Austin & Bevan, 2011;Deitz & Repp, 1973, 1974. Researchers have demonstrated the effectiveness of fullsession DRL across a variety of response topographies (e.g., talking out, Deitz & Repp, 1973; bids for attention, Austin & Bevan, 2011;excessive compliments and physical contact, Gadaire et al, 2017;rapid eating, Wright & Vollmer, 2002), populations (e.g., age ranges; e.g., Becraft et al, 2017, Gadaire et al, 2017, Otalvaro et al, 2020abilities and disabilities, e.g., Deitz & Repp, 1973, Gadaire et al, 2017, Piper et al, 2020, environments (e.g., general education and special education; e.g., Austin & Bevin, 2011;Dietz & Repp, 1973;Dietz & Repp, 1974) and in conjunction with other interventions (e.g., self-monitoring, Looney et al, 2018;response blocking, Wright & Vollmer, 2002;group contingencies, Groves & Austin, 2017). In settings with larger staff-to-student ratios, like a classroom, full-session DRL may be easier to implement than interval or spaced-responding DRL because fewer observers are required; therefore, a full-session DRL schedule may appeal to teachers and school staff (Austin & Bevan, 2011;Becraft et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…DRL has been used to successfully decrease neurotypical elementary children's excessive bids for teacher attention (e.g., Austin & Bevan, 2011;Becraft et al, 2017) and adult's excessive questions within a training center (e.g., Otalvaro et al, 2020) to appropriate levels. Additionally, it may be implemented with or without reinforcement signals (Becraft et al, 2017) which may also increase the ease of implementation and increase the efficacy (Austin & Bevan, 2011;Becraft et al, 2017;Becraft et al, 2017;Oltavaro et al, 2020;Piper et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that the treatment package was effective in reducing the rate of eating by 72%. Piper et al (2019) compared performances of a spaced-responding DRL contingency, and a full-session DRL contingency on arbitrary responses while using a reversal design in a classroom with four participants diagnosed with ASD. The results demonstrated that the spaced-responding variant yielded an increase of 73% improvement, and full-session yielded a 49% improvement in the reduction of arbitrary responses.…”
Section: Spaced-respondingmentioning
confidence: 99%